(untitled) (Research, Society and Development, 2021)
Purpose: To verify the relationship between the results of the “Foam-Laser” Dynamic Posturography, falls and concern about falling in elderly practitioners of physical exercise. Methodology: Cross-sectional, observational, descriptive study. The population consisted of elderly people of both sexes, regular practitioners of physical exercise. The elderly answered the anamnesis, the instrument Falls Efficacy Scale International (FES-I-Brazil), to verify the concern with falling and were evaluated using the “Foam-Laser” Dynamic Posturography to assess the systems for maintaining body balance. Results: 109 individuals were included in the sample, of which 89 are female and 20 are male, with a mean age of 72.1±6.2 years. The results of the FES-I-Brasil showed minimal concern about falling, regardless of age. Among elderly fallers (24.8%), the mean score on the FES-I-Brazil was 24.7±9.40 points and among non-fallers (75.2%) it was 23.9±6.42 points. With regard to posturography, it was found that the elderly aged 80 years or more had a worse performance in the TOS V test (Sensory Organization Test) and vestibular predominance when compared to the elderly aged 60 to 69 years. It was found that the evaluated elderly showed mean values lower than the cutoff point proposed in the specialized literature in all sensory analysis tests when compared to the normal values found in the literature, except in the TOS V test for younger elderly people. Conclusion: There was no relationship between the assessments performed, regardless of the occurrence or not of falls among the elderly assessed.